Ginsenoside Rc, as an FXR activator, alleviates acetaminophen-induced hepatotoxicity via relieving inflammation and oxidative stress - Yadi Zhong; Yadi Zhong; Yingjian Chen; Zhisen Pan; Kaijia Tang; Guangcheng Zhong; Jingyi Guo; Tianqi Cui; Tianyao Li; Siwei Duan; Xiaoying Yang; Yong Gao; et al. (Frontiers Media S.A., 2022)
Acetaminophen (APAP) intake leads to excessive NAPQI deposition, stimulating inflammatory and oxidative stress and causing fatal liver injury. However, the detailed molecular mechanism involved is unknown, and effective therapeutic approaches remain insufficient. In this study, we discovered that treatment with ginsenoside Rc can prevent the inflammatory response caused by APAP and oxidative stress in mouse primary hepatocytes (MPHs), along with the corresponding changes in related genes. Additionally, Ginsenoside Rc effectively alleviates APAP-induced cellular apoptosis and NAPQI accumulation in MPHs. In vivo, Ginsenoside Rc administration remarkably attenuates APAP-induced hepatotoxicity, repairing liver damage and improving survival. Moreover, Ginsenoside Rc treatment modulates genes involved in APAP metabolism, leading to a decrease in NAPQI and resulting in the alleviation of fatal oxidative stress and inflammatory response after APAP exposure, along with the expression of their related indicators. Furthermore, our RNA-seq and molecular docking analysis implies that FXR expression and FXR transcriptional activity are stimulated by Ginsenoside Rc treatment. Notably, due to the lack of FXR in mice and MPHs, ginsenoside Rc can no longer play its original protective role against hepatotoxicity and cell damage caused by APAP, and it is difficult to improve the corresponding survival rate and prevent hepatic apoptosis, NAPQI generation, fatal oxidative stress, and the inflammatory response induced by APAP and the expression of related genes. In summary, our results indicate that Ginsenoside Rc could act as an effective FXR activator and effectively regulate FXR-induced antioxidant stress and eliminate inflammation while also having an anti-apoptotic function.